2020
DOI: 10.1371/journal.pone.0230315
|View full text |Cite
|
Sign up to set email alerts
|

Do dog breeds differ in pain sensitivity? Veterinarians and the public believe they do

Abstract: Humans do not respond to the pain of all humans equally; physical appearance and associated group identity affect how people respond to the pain of others. Here we ask if a similar differential response occurs when humans evaluate different individuals of another species. Beliefs about pain in pet dogs (Canis familiaris) provide a powerful test, since dogs vary so much in size, shape, and color, and are often associated with behavioral stereotypes. Using an on-line survey, we asked both the general public and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 42 publications
5
35
0
Order By: Relevance
“…Given the pathophysiological similarities between human and canine osteoarthritis ( Meeson et al, 2019 ), a similarly extensive range of pain morphologies could be experienced by dogs. This may go some way to account for the wide range and intermittent nature of behavioural changes owners describe, as may the recent finding that owners and veterinary surgeon perceive there to be breed differences in pain experience ( Gruen et al, 2020 ). Educating owners about the wide range of behavioural signs to look for and their potential relationship with pain may decrease the time to initial veterinary presentation and since this research was conducted, a wide-ranging awareness campaign for owners has been launched ( Canine Arthritis Management, 2020 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Given the pathophysiological similarities between human and canine osteoarthritis ( Meeson et al, 2019 ), a similarly extensive range of pain morphologies could be experienced by dogs. This may go some way to account for the wide range and intermittent nature of behavioural changes owners describe, as may the recent finding that owners and veterinary surgeon perceive there to be breed differences in pain experience ( Gruen et al, 2020 ). Educating owners about the wide range of behavioural signs to look for and their potential relationship with pain may decrease the time to initial veterinary presentation and since this research was conducted, a wide-ranging awareness campaign for owners has been launched ( Canine Arthritis Management, 2020 ).…”
Section: Discussionmentioning
confidence: 98%
“…Owners could be unaware that osteoarthritis affects dogs or might struggle to recognise relevant behavioural indicators. Pain behaviours may be confused with a behaviour problem ( Mills et al, 2020 ), and some dog breeds are perceived by the public to be less pain sensitive than others ( Gruen et al, 2020 ). Owners who are aware of a problem may delay their dog’s presentation to a veterinary practice if they are uncertain or fearful of the veterinary surgeon’s recommended actions ( Belshaw et al, 2016a ; Christiansen et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…It may also indicate that musculoskeletal disorders in SBTs appear relatively mild, therefore “stiffness” may not be categorised at a further diagnostic level. Indeed, veterinarians rated Pitbull breed types with low pain sensitivity compared with other breeds and gave lower ratings for Pitbull breed types than the general public [ 47 ]. Given the prevalence of elbow dysplasia in SBTs previously reported as 31.3–33.3% [ 48 , 49 ] and the documented stoicism of the breed [ 50 ], it might be that “stiffness” is indicative of an underlying condition that may warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this are data from another study 37 which examined genetic differences between the Australian Kelpie and the related Australian Working Kelpie dog and found that the Working Kelpie has been bred primarily for gene loci influencing pain perception and fear memory formation. Indeed, there are strong perceptions about breed differences in sensitivity, although those perceptions differ between the general public and veterinarians 38 …”
Section: Discussionmentioning
confidence: 99%